Where be dragons? - Miguel Andrade (Medievalista)
Dragons are frequent presences in Old Norse-Icelandic sagas, composed between the 13th and 15th centuries. The locations where dragons appear have been so far observed mainly under the lens of their relation to centre/periphery dynamics and regarding the borders of the otherworldly. Less focus has been devoted to the physical environments that dragons occupy, whether the ones they habitually inhabit or the ones they turn uninhabitable. The habitat of dragons encompasses a variety of natural environments throughout Old Norse-Icelandic literature. In this article, we will focus on the literary landscapes (sometimes informed by real geographies familiar to the authors, depending on setting), which surround dragons in the sagas, namely topographical features, weather phenomena, times of day and seasons. The main goal will be to define which landscapes saga dragons are mainly found in, and reflect on how dragons interact with their surroundings, altering their landscapes, most often through destructive means and making spaces into non-shared zones. As descriptions of dragon surroundings are often scarce in detail, this study intends to take a broad-scope approach to the available corpus of sagas with dragons in them, combing 55 dragon occurrences across 38 sagas and þættir (“tales, episodes”) for landscape-oriented vocabulary. It will focus on “legendary sagas” and "chivalric sagas" due to prevalence of the material, but also include episodes from "sagas of Icelanders", "kings’ sagas" and other texts adjacent to those genres.